2015
DOI: 10.1152/ajplung.00214.2015
|View full text |Cite
|
Sign up to set email alerts
|

Experimental progressive emphysema in BALB/cJ mice as a model for chronic alveolar destruction in humans

Abstract: Limjunyawong N, Craig JM, Lagassé HA, Scott AL, Mitzner W. Experimental progressive emphysema in BALB/cJ mice as a model for chronic alveolar destruction in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 88 publications
(95 reference statements)
6
40
1
Order By: Relevance
“…As alveolar fibroblasts are the major p19 ARF ‐expressing cells in the lung (Figure 1f; Hashimoto et al, 2016), these cells likely affected the expression of MMP‐12 and TIMP‐2 cell nonautonomously through SASP. Consistent with previous findings (Limjunyawong et al, 2015; Ueno et al, 2015), the expression of these genes was mostly diminished after 3 weeks, and DT also had a minor effect on these genes at this time point (Figures 5b and S5b). Collectively, these results suggest that the presence of p19 ARF ‐expressing cells in lung tissues facilitates the accumulation of inflammatory cells during the early phase of a PPE challenge, which promotes the development of emphysema‐associated pathologies.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…As alveolar fibroblasts are the major p19 ARF ‐expressing cells in the lung (Figure 1f; Hashimoto et al, 2016), these cells likely affected the expression of MMP‐12 and TIMP‐2 cell nonautonomously through SASP. Consistent with previous findings (Limjunyawong et al, 2015; Ueno et al, 2015), the expression of these genes was mostly diminished after 3 weeks, and DT also had a minor effect on these genes at this time point (Figures 5b and S5b). Collectively, these results suggest that the presence of p19 ARF ‐expressing cells in lung tissues facilitates the accumulation of inflammatory cells during the early phase of a PPE challenge, which promotes the development of emphysema‐associated pathologies.…”
Section: Resultssupporting
confidence: 92%
“…Although a significant change was observed in lung morphology and function 3 weeks after the administration of PPE (Figures 2 and 3), no significant difference was found in the number or composition of inflammatory cells in BALF among PPE‐ and/or DT‐treated samples at this time point (Figure S3). This result was expected because a single shot of PPE only has temporal effects on BALF cells in the C57BL/6J strain (Limjunyawong, Craig, Lagassé, Scott, & Mitzner, 2015; Ueno et al, 2015). Therefore, we analyzed BALF cells at an earlier time point after the administration of PPE.…”
Section: Resultsmentioning
confidence: 85%
“…We have reported a simple approach that circumvents the problems with measurement of diffusing capacity in mice (Fallica, et al, 2011, Limjunyawong, et al, 2015c). This procedure results in a very reproducible measurement, that is sensitive to a host of pathologic changes in the lung phenotype, including being able to follow the emphysematous changes over time(Limjunyawong, et al, 2015a). …”
Section: B Mouse Models Of Emphysemamentioning
confidence: 99%
“…Immediately after administration of elastase, the population of lung-resident macrophages decreases, but they quickly recover. Macrophages, eosinophils, and lymphocytes (both CD4 and CD8 T cells) remain elevated for weeks in the post-elastase lung and the elevation of these cells is associated with rapid and worsening lung damage that can be visualized histologically (Limjunyawong, Craig, Lagasse, Scott and Mitzner, 2015a) and measured by decrements in lung function (Figure 2 and Figure 3). At later times, there are increased numbers of CD4+ and CD8+ T cells with significant enlargement of airspaces within 21 days (Kurimoto, Miyahara, Kanehiro, Waseda, Taniguchi, Ikeda, Koga, Nishimori, Tanimoto, Kataoka, Iwakura, Gelfand and Tanimoto, 2013) (Figure 2).…”
Section: Innate and Adaptive Immunity In The Pathogenesis Of Emphymentioning
confidence: 99%
“…However, as in CS models, these effects are dependent on several factors, including strain; enzyme dose at each instillation; and number of elastase challenges (Figure 2). Limjunyawong et al recently reported that BALB/C mice are more sensitive than C57BL/6J to elastase injury, as demonstrated by significantly greater mortality, weight loss, decline in lung function, and loss of alveolar tissue [89]. Regarding dose and number of elastase challenges, Lüthje et al demonstrated that mice subjected to five elastase administrations with a 1-week interval between them developed not only a more severe alveolar destruction, but also systemic associated with systemic effects [36].…”
Section: Elastase Instillationmentioning
confidence: 99%